Елементи національно-мовної картини світу українців у перекладах А. Кримського творів східної літератури - Стельмах, Богдана; Stelmakh, Bohdana (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті йдеться про відображення національно-мовної картини світу в перекладних творах А. Кримського поезії класиків східної літератури (Сааді, Хафіза, Хайяма), народних пісень з турецької, перської, арабської та інших мов, яка виявляється у використанні традиційних для українців народнопоетичних образів, емоційно забарвленої лексики, діалектизмів, ритмомелодики тощо.The article deals with the representation of the national linguistic picture of the world in Ahatanhel Krymsky’s translations of the classical Oriental poets (Saadi, Hafez, Khayyam) and folk songs from Turkish, Farsi, Arabic and other languages, which manifests itself in traditional Ukrainian folk poetic imagery, emotionally coloured vocabulary, dialecticisms, rhythm, melody, etc. The article clearly shows how the poetry in translation reflects not only the features of worldview, stylistic manner of the author of the original, but also individual linguistic worldview of interpreter, their interweaving and complementarily, giving rise to new work of art, more or less different from the original.
Elements of national linguistic worldview of Ukrainians in translations of works by A. Krymskiy of Oriental Literature
Keywords: національно-мовна картина світу; фразеологізми; діалектизми; емоційно забарвлена лексика; national linguistic picture of the world; phraseological units; dialecticisms; emotionally coloured vocabulary